2005
DOI: 10.1038/labinvest.3700223
|View full text |Cite
|
Sign up to set email alerts
|

Frequent LOH on 22q12.3 and TIMP-3 inactivation occur in the progression to secondary glioblastomas

Abstract: Frequent allelic losses on the long arm of chromosome 22 (22q) in gliomas indicate the presence of tumor suppressor gene (TSG) at this location. However, the target gene(s) residing in this chromosome are still unknown and their putative roles in the development of astrocytic tumors, especially in secondary glioblastoma, have not yet been defined. To compile a precise physical map for the region of common deletions in astrocytic tumors, we performed a high-density loss of heterozygosity (LOH) analysis using 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 34 publications
5
50
0
9
Order By: Relevance
“…Silencing of TIMP3 through promoter hypermethylation has been associated with poor prognosis in a range of human cancers including kidney, brain, colon (Bachman et al, 1999), non-small cell lung (Zochbauer-Muller et al, 2001) and meningiomas (Barski et al, 2010). Loss of TIMP3 expression, through loss of heterozigosity on chromosome 22q, is frequently observed in various cancers, such as secondary glioblastoma (Nakamura et al, 2005) and clear renal cell carcinomas (Masson et al, 2010). Evidence is emerging that downregulation of TIMP3 expression in tumors can be achieved also through deregulation of microRNAs, as TIMP3 is a target of several microRNAs upregulated in human tumors such as miR21, miR181b, miR221 and 222 (Gabriely et al, 2008;Garofalo et al, 2009;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of TIMP3 through promoter hypermethylation has been associated with poor prognosis in a range of human cancers including kidney, brain, colon (Bachman et al, 1999), non-small cell lung (Zochbauer-Muller et al, 2001) and meningiomas (Barski et al, 2010). Loss of TIMP3 expression, through loss of heterozigosity on chromosome 22q, is frequently observed in various cancers, such as secondary glioblastoma (Nakamura et al, 2005) and clear renal cell carcinomas (Masson et al, 2010). Evidence is emerging that downregulation of TIMP3 expression in tumors can be achieved also through deregulation of microRNAs, as TIMP3 is a target of several microRNAs upregulated in human tumors such as miR21, miR181b, miR221 and 222 (Gabriely et al, 2008;Garofalo et al, 2009;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez- Gomez et al (2003aGomez et al ( , 2003b have shown that the promoter region of this gene is hypermethylated in glioblastomas, especially in secondary glioblastomas, and in medulloblastomas. Nakamura et al (2005) have also found that the loss of heterozygosity in region 22q12.3, the region containing the TIMP-gene, is a frequent event in glioblastomas. These authors also suggested that these molecular alterations may be the primary cause of decreased expression of TIMP-3 in high-grade astrocytic tumors.…”
Section: The Role Of Timps In the Progression Of Astrocytic Tumorsmentioning
confidence: 99%
“…These authors also suggested that these molecular alterations may be the primary cause of decreased expression of TIMP-3 in high-grade astrocytic tumors. Nakamura et al (2005) have shown that hypermethylation of TIMP-3, and the consequent reduced expression of the gene, is an important factor in the poor survival of patients affected by highly malignant tumors.…”
Section: The Role Of Timps In the Progression Of Astrocytic Tumorsmentioning
confidence: 99%
“…Frequent allelic losses on 22q indicating the presence of tumor suppressor genes have been found in primary and secondary glioblastomas [69]. LOH of 22q identified two sites of minimally deleted regions at 22q12.3-13.2 and 22q13.31 in primary glioblastomas and in most of the secondary glioblastomas.…”
Section: Deletionsmentioning
confidence: 99%
“…As its name implies, expression of TIMP-3 inhibits metalloprotease activity and impair glioblastoma migration and invasiveness [70]. Expectedly, deletion of TIMP-3 enhances glioblastoma invasiveness [69].…”
Section: Deletionsmentioning
confidence: 99%